Trastuzumab deruxtecan versus chemotherapy for patients with HER2-low advanced breast cancer: A US-based cost-effectiveness analysis - Zhu, Youwen; Liu, Kun; Zhu, Xiaolu; Qin, Qun; Zhu, Hong (Frontiers in Pharmacology, 2022)
Background: In recent years, the rise of antibody-drug conjugates (ADCs) has changed the treatment paradigm for patients with HER2-low advanced breast cancer (ABC). DESTINY-Breast04 (NCT03734029) demonstrated the antitumor activity of trastuzumab-deruxtecan (T-DXd). However, the balance between the efficacy and cost of T-DXd remains undefined. Consequently, there is a great need to assess the cost-effectiveness of T-DXd for patients with HER2-low ABC compared with chemotherapy. Methods: The Markov decision-analytic model with a time horizon of 15 years was employed to estimate the costs and clinical efficacy of trials with the administration of T-DXd in contrast with chemotherapy alone as a later-line therapy in a group of patients with hormone receptor-positive (HR+) or negative (HR-) HER2-low ABC. The US payer perspective was taken into account when factors like medical lifetime expenditure, incremental cost-effectiveness ratios (ICERs) and quality-adjusted life-years (QALYs) were calculated. Sensitivity analyses were used to determine the model’s stability. A subgroup analysis was also conducted on HR+/ HER2-low Cohort. Results: T-DXd was associated with an improvement of 0.543, 0.558, and 0.789 QALYs compared with treatment with chemotherapy for overall, HR+, and HR- HER2-low patients, respectively. However, incorporating T-DXd into later-line therapy led to increase costs (161,406, 177,907, and 155,757), causing the ICER for T-DXd to be 296,873, 318,944, and 197,355 per QALY. The cost of T-DXd and the patient’s weight were the most influential factors for ICER. T-DXd being the dominant strategy is about 1.5%, 0.5%, and 28.0% in overall, HR+, and HR- HER2-low ABC patients, respectively. In addition, T-DXd regimen was not cost-effective in all subgroups. Conclusion: Compared with chemotherapy, T-DXd was not cost-effective for patients with HER2-low ABC in the US. However, it can provide more health benefits to patients with HR+/ HER2-low ABC.